Planning early childhood audiologic intervention programs on a regional scale: introduction to an Italian study. - Orzan, E; Ciciriello, E (Acta Otorhinolaryngol Ital, 2016)
Non-uniform, late, or inappropriate care of childhood with permanent hearing impairment (PHI) predisposes many children to develop communicative- behaviour problems and impaired psychosocial adjustment that can persist in adolescence and adulthood.In March 2014, the CCM (Centro Controllo Malattie or Disease Control Centre) of the Italian Ministry of Health funded a project entitled " Preventing Communication Disorders: a Regional Program for Early Identification, Intervention and Care of Hearing Impaired Children". The project involved 5 tertiary centres with UNHS programs formally approved by the Region. The main purpose of the project is to define and launch an integrated regionally-based public health model for identification, diagnosis and intervention of childhood PHI. The first phase of the project investigated the state of art and produced recommendations for positive changes in identification, diagnosis, therapy and care of childhood PHI in Italy, taking into account diagnostic and treatment innovations, family empowerment, treatment alliance and an interdisciplinary approach. Recommendations drawn from this initial phase will represent the basis for a regional system for early intervention that is validated, integrated and shared between the five regions.